Characteristics of Pediatric Performance on a Test Battery Commonly Used in the Diagnosis of Central Auditory Processing Disorder - Weihing, Jeffrey; Guenette, Linda; Chermak, Gail; Brown, Mallory; Ceruti, Julianne; Fitzgerald, Krista; Geissler, Kristin; Gonzalez, Jennifer; Brenneman, Lauren; Musiek, Frank (Journal of the American Academy of Audiology, 2015)
Background: Although central auditory processing disorder (CAPD) test battery performance has been examined in adults with neurologic lesions of the central auditory nervous system (CANS), similar data on children being referred for CAPD evaluations are sparse.Purpose: This study characterizes CAPD test battery performance in children using tests commonly administered to diagnose the disorder. Specifically, this study describes failure rates for various test combinations, relationships between CAPD tests used in the battery, and the influence of cognitive function on CAPD test performance and CAPD diagnosis. A comparison is also made between the performance of children with CAPD and data from patients with neurologic lesions of the CANS.Research Design: A retrospective study.Study Sample: Fifty-six pediatric patients were referred for CAPD testing.Data Collection and Analysis: Participants were administered four CAPD tests, including frequency patterns (FP), low-pass filtered speech (LPFS), dichotic digits (DD), and competing sentences (CS). In addition, they were given the Wechsler Intelligence Scale for Children (WISC). Descriptive analyses examined the failure rates of various test combinations, as well as how often children with CAPD failed certain combinations when compared with adults with CANS lesions. A principal components analysis was performed to examine interrelationships between tests. Correlations and regressions were conducted to determine the relationship between CAPD test performance and the WISC.Results: Results showed that the FP and LPFS tests were most commonly failed by children with CAPD. Two-test combinations that included one or both of these two tests and excluded DD tended to be failed more often. Including the DD and CS test in a battery benefited specificity. Tests thought to measure interhemispheric transfer tended to be correlated. Compared with adult patients with neurologic lesions, children with CAPD tended to fail LPFS more frequently and DD less frequently. Both groups failed FP with relatively equal frequency.Conclusions: The two-test combination that showed the highest failure rate for children with CAPD was LPFS-FP. Comparison with adults with CANS lesions, however, suggests that the mechanisms underlying LPFS performance in children need to be better understood. The two-test combination that showed the next highest failure rates among children with CAPD and did not include LPFS was CS-FP. If it is desirable to use a dichotic measure that has a lower linguistic load than CS then DD can be substituted for CS despite the slightly lower failure rate of the DD-FP battery.
Keywords: central auditory processing disorder; dichotic listening; temporal processing; monaural low redundancy; neuro-audiology